Optimal mission abort policy for systems subject to random shocks based on virtual age process - Qiu, Qingan; Cui, Lirong (Reliability engineering & system safety, 2019)
•Characterizing the impact of shocks on system failure behavior via random virtual age increments in normal and defective stages.•Developing a duration-based mission abort policy based on the two-stage failure process.•Analytically deriving mission success probability and system survivability under the proposed stochastic failure process and mission abort policy.•Investigating the optimal mission abort policy balancing the tradeoff between mission success probability. Safety critical systems such as aircrafts, submarines and space stations are required to perform various missions. To enhance the survivability of such systems, a mission can be aborted when a certain malfunction or incident condition is satisfied and a rescue procedure should be activated. This paper develops a novel mission abort policy for systems experiencing both internal failure and external shocks. Failure process of the system can be divided into two stages from new to the initialization of a defect, and from that to failure. Motivated by the virtual age concept, the impact of external shocks is characterized by random virtual age increment in the two stages. We consider a policy where a mission is aborted if the duration in defective state is larger than a given threshold. Under the stochastic failure model and mission abort policy, mission success probability and system survivability are evaluated and the optimal abort threshold balancing the tradeoff between the system survivability and the mission success probability is investigated. A numerical example on a cooling system in chemical reactors is given to illustrate the applicability of the abort policy.